2006
DOI: 10.1136/oem.2005.020644
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study of the respiratory health of workers handling printing toner dust

Abstract: Background: Although recent case reports have suggested possible respiratory effects of solid toner dust inhalation, this hypothesis has not been verified by epidemiological studies. Objectives: To conduct a cross sectional study to evaluate the association between the biological indices of lung fibrosis and toner dust exposure in an occupational cohort handling solid toner dust in their work life. Methods: A total of 600 male toner workers and 212 control subjects were surveyed in terms of their subjective re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 7 publications
4
28
0
Order By: Relevance
“…This result is consistent with findings of Nakadate et al (2006). This may be related to the short length of employment.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This result is consistent with findings of Nakadate et al (2006). This may be related to the short length of employment.…”
Section: Discussionsupporting
confidence: 95%
“…It is therefore feasible that individuals working in the photocopy centers may be exposed to high levels of VOC and O 3 . To date, however, only one study has determined the adverse health effects of occupational exposure to pollutants emitted from photocopiers (Nakadate et al, 2006). This cross-sectional study was conducted to examine the potential adverse effects among a group of photocopy center workers in Kaohsiung City, Taiwan.…”
mentioning
confidence: 99%
“…Office laser printers are major emission sources of nanoparticles including carbon nanoparticles (He et al, 2007;Morawska et al, 2009). Cross sectional studies indicated a greater prevalence of radiographic abnormalities and decreased lung function in workers dealing with printing toner dust (Nakadate et al, 2006;Terunuma et al, 2009). And a recent case study demonstrated that carbon +nanoparticles aggregated under the mesothelium in the peritoneum along with inflammatory responses, and nanoparticles got distributed via lymphatic and blood circulation post inhalation into the lung (Dirk et al, 2010).…”
Section: Resultsmentioning
confidence: 95%
“…In chronic toxicity tests, although lung tumors occurred with intratracheal injection 4) , fibrosis of lungs was observed in all cases in the high-concentration exposure group in inhalation tests using rats, but lung tumors did not occur 5) . With regard to health impacts on humans, although there have been reports suggesting the possibility of siderosilicosis 6) and granulomatous pneumonitis 7,8) , there were no clear health impacts on the respiratory system in epidemiological studies using workers exposed to toner as subjects 9) . Even with regard to the mortality ratio, the standardized mortality ratios (SMRs) of workers exposed to toner were less than 1.0 for all cancers, lung cancer, respiratory disorders and cardiac disorders 10) .…”
Section: Discussionmentioning
confidence: 99%